Impact of urban expansion on grain production in the Japan Sea Rim region - Shen, Xiaoli; Zhang, Da; Nan, Ying; Quan, Yue; Yang, Fengru; Yao, Yuanhao (Frontiers in Earth Science, 2023)
The Japan Sea Rim (JSR) region is the core area for the future sustainable development of Northeast Asia. Effectively assessing the impact of urban expansion on grain production is of great significance for achieving sustainable development goals (SDGs), such as SDG2 Zero Hunger, and promoting sustainable development in Northeast Asia. Only a few studies have assessed the impact of urban expansion on grain production in the JSR. In this study, we initially analyzed urban expansion in the JSR for the period 1992 to 2050. Then, we assessed the impact of urban expansion on cropland net primary productivity (NPP) based on NPP data. Finally, we evaluated the impact of urban expansion on grain production in the JSR. The results indicated that urban land expanded from 21509 km²to 42501 km² in the JSR between 1992 and 2020 (an increase of 1.98 times), and the occupation of cropland caused by urban expansion resulted in a decrease of 2.21 million t in grain production. Urban land will continue to expand from 2020 to 2050, which will cause grain production to decrease by 1.68 (1.02–2.24) million t. China will experience the most serious loss of grain production, accounting for 62.93% (56.69–71.60%) of the total grain production loss in the JSR. Considering the situation for the period 1992–2020, the impact of urban expansion on grain production will be moderated in the future. Thus, the future grain production loss will be reduced by 24.18% (8.80–53.98%). However, future urban expansion will continue to have a negative impact on regional food security. Therefore, we suggest that urban development should be reasonably regulated and high-quality cropland should be protected. Meanwhile, we should strengthen international cooperation and optimize food and economic trade among different countries in the JSR to ensure food security and promote sustainable regional development.